Phycochemical and Biological Activities From Different Extracts of Padina antillarum (Kützing) Piccone - Samar, Juveria; Butt, Ghazala Yasmeen; Shah, Anis Ali; Shah, Adnan Noor; Ali, Sajad; Jan, Basit Latief; Abdelsalam, Nader R.; Hussaan, Muhammad (Frontiers in Plant Science, 2022)
Seaweeds are non-vascular, photosynthetic that inhabit the coastal regions commonly within rocky intertidal or submerged reef-like habitats and have been one of the richest and most promising sources of bioactive primary and secondary metabolites with antimicrobial properties. They selectively absorb elements like Na, K, Ca, Mg, I, and Br from the seawater and accumulate them in their thalli. Padina antillarum (Kützing) Piccone is a member of Phaeophycota and has remarkable phycochemistry as well as bioactivity. The phycochemical tests of the different extracts showed the presence of alkaloids, terpenoids, saponins, tannins, steroids, and phenols. The relative percentage of Oxirane, tetradecyl (C16H32O), and Cyclononasiloxane (C18H54O9Si9) are higher while Tetrasiloxane (C16H50O7Si8) is lowest in Gas Chromatography – Mass Spectrometry analysis. FRAP, %inhibition, the total antioxidant value of P. antillarum was higher in methanolic extract. Hexane, chloroform extracts showed no zone of inhibition against Bacillus subtilis, Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus, and Staphylococcus epidermidis. The methanolic extract of P. antillarum exhibits a maximum zone of inhibition against S. epidermidis (18.66 ± 0.09). Antifungal activity of the P. antillarum in hexane extract exhibited no zone of inhibition against Aspergillus niger and Penicillium notatum while the chloroform extract yields maximum zone (37 ± 0.012, 21.66 ± 0.03). Diabetes mellitus is one of the most familiar chronic diseases associated with carbohydrate metabolism. It is also an indication of co-morbidities such as obesity, hypertension, and hyperlipidemia which are metabolic complications of both clinical and experimental diabetes. The treatment of P. antillarum methanol extract in mice reduced the body weight loss, low level of triglycerides, and elevated HDL cholesterol level as compared to diabetic mice.